1999
DOI: 10.1002/(sici)1097-4636(19990905)46:3<305::aid-jbm1>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Plasmin degradation of fibrin coatings on synthetic polymer substrates

Abstract: The goal of this research was to evaluate the in vitro stability of fibrin coatings on polymeric materials in the presence of plasmin. Factor XIIIa-crosslinked and noncrosslinked fibrin layers were coated on three different polyurethane substrates: Corethane, Tegaderm, and a biodegradable polyurethane, PCL/HDI/Phe. Degradation assays indicated that crosslinking the fibrin coatings enhanced the stability of the coatings on both Tegaderm and PCL/HDI/Phe; however, the persistence of the coating on the woven Coret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…Fibrin is a biodegradable, biocompatible matrix protein involved in wound healing and can be produced from a patient’s blood and therefore does not initiate inflammation, tissue necrosis, or fibrosis [79, 89–91]. Jockenhoevel et al used molded fibrin gels as a potential scaffold for TE [79].…”
Section: Polymeric Scaffoldsmentioning
confidence: 99%
“…Fibrin is a biodegradable, biocompatible matrix protein involved in wound healing and can be produced from a patient’s blood and therefore does not initiate inflammation, tissue necrosis, or fibrosis [79, 89–91]. Jockenhoevel et al used molded fibrin gels as a potential scaffold for TE [79].…”
Section: Polymeric Scaffoldsmentioning
confidence: 99%
“…Before exposure to shear stress, the distribution of ECs was comparable for the uncoated or (PAH-PSS) 3 -PAH coated surfaces. After exposure to shear stress, the retention was quite larger for (PAH-PSS) 3 Several authors showed that exposure to low mechanical forces like shear stress orients cells toward flow direction and then improves ECs adhesion and retention in vivo [2,14,24,36,39,40,57]. Therefore, we tested the hypothesis that an exposure of the endothelialized PEMs coated graft to a preconditioning shear stress of 1 Pa for three hours before graft implantation could improve cell retention after implantation.…”
Section: Resultsmentioning
confidence: 96%
“…Compared to fibrin, a PSS/PAH film could resist quite longer to enzymatic degradations. Moreover, PEM films are also extremely thin and very easy to deposit inside small caliber vessels (<6 mm) in a reproducible way [3,15]. In a next step, we checked, in vivo, the patency of the endothelialized and coated grafts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, degradation and pitting of the film is attributed to release of reactive oxygen intermediate at the FC-cell interface. Platelet aggregation on fibrin surfaces has been reported (Skarja et al 1998) and degradation of fibrin proceeds by the action of plasmin (Bence et al 1999). Complete degradation of FC film was observed on 30 PID and hence it is concluded that it is biocompatible, biodegradable and can serve as a potential wound dressing material.…”
Section: Equilibrium Water Contentmentioning
confidence: 99%